The Success Factors of SME Business in Luangpabang Capital - HOONGSENGPHA, Soudtida; INDAVONG, Dalounny; PHUMMA, Somphone; SOMSACKSAYSOMPHENG, Oulavieng; PHENGSAVAT, Sitthivikone; KHOMTHAVONG, Phonepasith; SITTHIRAJVONGSA, Vilat; OUPRAVANH, Yothana (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
This research was conducted to determine “the success factors of SME business in Luangpabang capital”. The factors were categorized into 6 dimensions, for instance, organization management, entrepreneurs, political policy, social and cultural dimension, the economy as well as technological aspects. The key sample participants of this invesgiation were 351 Small and medium-sized enterprises (SMEs) (SMEs) business owners in LuangPrabang City. The main instrument applied in this study was questionnaire which included factors leading to success in SMEs in LuangPrabang City. In addition, the data was analyzed by the Pearson Product Moment Correlation Coefficient and Stepwise Multiple Regression Analysis. The finding indicated that there was statistically significant correlation among the influence factors behind the success of SMES in LuangPrabang City, which statististical significance was 0.05 abd 0.01 for organization management factor (x1) and entrepreneurship factor(X2) and in terms of socio-cultural factor (x4) and economic factor (x5) which statistical significance was at 0.01 and 0.05 respectively. Statistical Prediction of the factors contributing to SMEs business success in LuangPrabang City: In the form of raw scores were: Y = 0.968+ 0.115 X1+0.101X2+0.448X4 + 0.047X5 In the form of standard scores were: Z= 0.147 X1+0.135X2+0.632X4 + 0.072X5